2015
DOI: 10.3928/01477447-20150402-57
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes in Patients Undergoing Revision Rotator Cuff Repair With Extracellular Matrix Augmentation

Abstract: Outcomes following revision surgery for failed rotator cuff repairs are far less predictable than and are associated with decreased patient satisfaction compared with primary repairs. Extracellular matrix augmentation (ECM) may improve the biologic potential for healing during revision repair. The authors examined clinical outcomes and healing rates based on postoperative imaging of patients who underwent revision open rotator cuff repair with an ECM patch for symptomatic recurrent rotator cuff tear. Twenty-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…After 112 months, the augmentation with ECM patches showed no clinical improvements in comparison to the repair without augmentation, found in literature data, showing also a 42% of poor outcomes (Sears et al, 2015).…”
Section: Rotator Cuffmentioning
confidence: 65%
See 2 more Smart Citations
“…After 112 months, the augmentation with ECM patches showed no clinical improvements in comparison to the repair without augmentation, found in literature data, showing also a 42% of poor outcomes (Sears et al, 2015).…”
Section: Rotator Cuffmentioning
confidence: 65%
“…Thirty percent of the studies regarding RCT reached a maximum follow-up of 12 months (Barber, 2016;Bergeson et al, 2012;Encalada-Diaz et al, 2011;Rodeo et al, 2012;Rotini et al, 2011;Weber et al, 2013), while 1 (Basiglini et al, 2010) study evaluated outcomes at 12 months in Achilles tendon ruptures. Studies that exceeded 36 months of follow-up were five in RCT studies (44, 60, 68, or 112 months and 16 years;Badhe et al, 2008;Barber et al, 2011;Russo et al, 2011;Sears et al, 2015;Wong et al, 2010) and six (41, 60, 68, 81, and 117 months;Bibbo, 2010;Elias et al, 2009;Esenyel et al, 2014;Ibrahim, 2009;Nilsson-Helander et al, 2008;Wegrzyn et al, 2010) in Achilles tendon ones. Only one study showed a follow-up earlier than 12 months in RCT (Snyder et al, 2009) and five studies in Achilles tendon (3, 6, and 9 and 11 months;Branch, 2011;DeCarbo et al, 2010;Kearney & Costa, 2010;Ollivere et al, 2014;Stover et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high rate at which these surgeries are performed and regardless of advances in technology and surgical techniques, retear after rotator cuff surgery remains a common problem. It has been reported that recurrent tears after rotator cuff repair range between 20% and 40% for small‐to‐medium tears and as high as 94% for large or chronic tears . Predisposing factors for retear include patient's age, size of tear, acuity/chronicity of tear, tendon quality, and muscle atrophy/fatty infiltration, all of which contribute to a poor capacity for healing—the fundamental culprit for failure of surgically reconstructed rotator cuff tendons .…”
Section: Introductionmentioning
confidence: 99%
“…small-to-medium tears and as high as 94% for large or chronic tears. [6][7][8][9][10] Predisposing factors for retear include patient's age, size of tear, acuity/chronicity of tear, tendon quality, and muscle atrophy/fatty infiltration, all of which contribute to a poor capacity for healing-the fundamental culprit for failure of surgically reconstructed rotator cuff tendons. 3,8 Healing of a torn rotator cuff is an extremely complex process, focused around the tendon-to-bone interface, called the enthesis.…”
Section: Introductionmentioning
confidence: 99%